Gut dysbiosis is associated with the reduced exercise capacity of elderly patients with hypertension. Issue 12 (December 2018) - Yu, Yanbo; Mao, Genxiang; Wang, Jirong; Zhu, Liyue; Lv, Xiaoling; Tong, Qian; Fang, Yefei; Lv, Yinxiang; Wang, Guofu
Abstract Hypertension is a global health issue, and a reduced exercise capacity is unavoidable for older people. According to recent clinical studies, the intestinal microbiota play a crucial role in the pathogenesis of many human diseases. We investigated whether specific alterations in the gut microbiota contribute to the reduced exercise capacity of elderly patients with hypertension. This study enrolled 56 subjects, and all patients performed a cardiopulmonary exercise test and underwent fecal bacteria sequencing (16 s ribosomal RNA V4 region). According to peak oxygen uptake values, patients were divided into three groups (WeberA = 19, WeberB = 20, and WeberC = 17). The alpha diversity was not significantly different among the three groups. Regarding the beta diversity, Weber A samples were separate from the other two groups in the nonmetric multidimensional scaling ordination plot (ANOSIM pairwise comparisons generated anR > 0.5;p < 0.05). The abundance of Betaproteobacteria, Burkholderiales, Alcaligenaceae, Faecalibacterium and Ruminococcaceae was diminished in subjects with a reduced exercise capacity (LDA score > 4.0).Escherichia coli are a primary producer of trimethylamine and inflammation in the human gut, and the abundance of this bacteria was increased in patients with a reduced exercise capacity (LDA score > 4.0). On the other hand, Lachnospiraceae-Eubacterium_hallii _group, Lachnospiraceae-Lachnoclostridium, Lachnospiraceae-Blautia -Ruminococcus _sp__5_1_39BFAA, and Ruminococcaceae-Faecalibacterium belong to the order Clostridiales that are likely to produce short-chain fatty acids (LDA score > 4.0), and some of these species were enriched in the Weber B or Weber C group in multiple comparisons. Our data pointed to an altered gut microbiota as a potential contributor to the pathogenesis and progression of the reduced exercise capacity of elderly patients with hypertension.